1969
DOI: 10.1115/1.3591786
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Vibrations of a Beam With Pinned Ends

Abstract: This paper describes theoretical and experimental investigations of the large-amplitude vibrations of a flexible beam simply supported on a nearly rigid base. The beam is designed to minimize most secondary effects, such as transverse shear flexibility, rotatory inertia, and nonlinearities in curvature and in the stress-strain curve. Detailed attention is given to quantitative verification of the assumptions made in deriving the equation of motion. Three different approaches are used to solve the equation: ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…As in the previous research of Yu [144] and Ray and Bert [145], it is assumed that the effect of coupling among individual vibration modes is not quantitatively significant, which has been confirmed by comparing analytical predictions with experimental results.…”
Section: Effects Of Localized Loadsmentioning
confidence: 73%
“…As in the previous research of Yu [144] and Ray and Bert [145], it is assumed that the effect of coupling among individual vibration modes is not quantitatively significant, which has been confirmed by comparing analytical predictions with experimental results.…”
Section: Effects Of Localized Loadsmentioning
confidence: 73%
“…In [1] it was shown that equations (8) are solved by the Jacobian elliptic functions u m = cn(wmt + am, km) (11) in which the natural frequencies (o m and the moduli k m are 2= c~m and k 2= 1-.…”
Section: Separation Of the Modesmentioning
confidence: 99%
“…Other reports of investigations were given by Eisley [6], Morris [7], Srinivasan [8], Evenson [9], Bennett and Eisley [10] and Ray and Bert [11]. A succinct summary of developments through 1972 is given by Busby and Weingarten [12], and an encyclopaedic listing of references to work both immediately and closely related is to be found in the research monograph Nonlinear Oscillations, by Ali H. Nayfeh and Dean T. Mook [13].…”
Section: Introductionmentioning
confidence: 99%
“…Employing the elliptic integral solution, he investigated the nonlinear vibrations of hinged-hinged beams with axially immovable ends. This issue was afterwards addressed by several authors using perturbation and Ritz-Galerkin methods (Srinivasan, 1965;Evensen, 1968;Ray and Bert, 1969). There can be found some newer analytical studies on the nonlinear vibrations of beam, which seem to be useful, such as (Azrar et al, 1999;Emam, 2009;Emam and Nayfeh, 2009;Pirbodaghi et al, 2009).…”
Section: Introductionmentioning
confidence: 97%